Patterns of gene flow and selection across multiple species of Acrocephalus warblers: footprints of parallel selection on the Z chromosome - Reifová, Radka; Majerová, Veronika; Reif, Jiří; Ahola, Markus; Lindholm, Antero; Procházka, Petr (BMC evolutionary biology, 2016)
BACKGROUND: Understanding the mechanisms and selective forces leading to adaptive radiations and origin of biodiversity is a major goal of evolutionary biology. Acrocephalus warblers are small passerines that underwent an adaptive radiation in the last approximately 10 million years that gave rise to 37 extant species, many of which still hybridize in nature. Acrocephalus warblers have served as model organisms for a wide variety of ecological and behavioral studies, yet our knowledge of mechanisms and selective forces driving their radiation is limited. Here we studied patterns of interspecific gene flow and selection across three European Acrocephalus warblers to get a first insight into mechanisms of radiation of this avian group. RESULTS: We analyzed nucleotide variation at eight nuclear loci in three hybridizing Acrocephalus species with overlapping breeding ranges in Europe. Using an isolation-with-migration model for multiple populations, we found evidence for unidirectional gene flow from A. scirpaceus to A. palustris and from A. palustris to A. dumetorum. Gene flow was higher between genetically more closely related A. scirpaceus and A. palustris than between ecologically more similar A. palustris and A. dumetorum, suggesting that gradual accumulation of intrinsic barriers rather than divergent ecological selection are more efficient in restricting interspecific gene flow in Acrocephalus warblers. Although levels of genetic differentiation between different species pairs were in general not correlated, we found signatures of apparently independent instances of positive selection at the same two Z-linked loci in multiple species. CONCLUSIONS: Our study brings the first evidence that gene flow occurred during Acrocephalus radiation and not only between sister species. Interspecific gene flow could thus be an important source of genetic variation in individual Acrocephalus species and could have accelerated adaptive evolution and speciation rate in this avian group by creating novel genetic combinations and new phenotypes. Independent instances of positive selection at the same loci in multiple species indicate an interesting possibility that the same loci might have contributed to reproductive isolation in several speciation events.
Keywords: Biodiversity; Genetic Speciation; Sex Chromosomes; fenotyp; Male; Phenotype; pohlavní chromozomy; genetická variace; tok genů; Europe; biodiverzita; biologická evoluce; mužské pohlaví; zpěvní ptáci; reprodukční izolace; vznik druhů (genetika); Selection, Genetic; Evropa; selekce (genetika); Animals; ženské pohlaví; Biological Evolution; zvířata; Hybridization, Genetic; Songbirds; hybridizace genetická; Genetic Variation; Female; Reproductive Isolation; Gene Flow